The optimization of Fenugreek seeds (Trigonella foenum-graecum L.) extraction by response surface methodology based on β-Sitosterol - Zahra Tofighi; Mohammad Reza Khoshayand; Masoud Besati; Mostafa Pirali Hamedani; Abbas Hadjiakhoondi; Ali Khorshidi; Arian Salimi; Saied Goodarzi (Institue of Medicinal Plants, ACECR, 2023)
Background: Fenugreek is one of the most widely used medicinal plants in terms of therapeutic properties, and numerous pharmacological effects have been found in various studies. Fenugreek seed extract contains many effective substances, including phytosterols (mainly β-Sitosterol). Objective: This investigation was conducted to determine the optimal extraction method for fenugreek seeds based on the amount of β-Sitosterol detected on HPLC using a response surface methodology (RSM). Methods: At first, the appropriate solvent was selected. The main variables affecting the extraction efficiency, including temperature, time, solvent percentage, and the ratio of solvent to powder, were investigated to optimize the best method. Optimizing the number of 29 experiments determined that extraction was done using the dynamic maceration method. After finding the optimized method, the extracts were injected into the HPLC device three times to determine the amount of total β-Sitosterol. Then it was modelled, and the final formula was obtained. Results: The analysis of results were shown that the optimal extract (based on the amount of total β-Sitosterol and weight), using the dynamic maceration extraction method with 96 % ethanol at a temperature of 44 ˚C, a duration of 30 minutes, a solvent percentage of 70 % and a ratio of solvent to powder of 7:1 was obtained. Conclusion: The findings suggest the, this method seams the most efficient for maximum extraction of the β-Sitosterol compound from fenugreek seeds.